Pengaruh Citra Merek, Harga, Dan Kualitas Produk Terhadap Loyalitas Konsumen Melalui Kepuasan Konsumen Sebagai Variabel Intervening - Oktarahman, Rizal; , Dr,Soepatini,M.Si (2016)
The purpose of this study to determine an empirical consumer Arina cake home industry with the influence of brand image, price and quality of products on consumer loyalty through customer satisfaction as an intervening variable. While the methods used in this study using the methods of data analysis: test instrument, the classical assumption test, test path analysis, and hypothesis testing. Based on the test results the instrument variables x and y is declared valid, while the results of the classical assumption variables x and y are also no problems occur. But based on results of test analysts and test hypotheses path can be determined by t test for customer satisfaction is happening is significant relationship between the variables of brand image, price, and product quality to customer satisfaction though the brand image experiencing significant negative results. And the results of the t test for consumer loyalty is the happening effect was not significant between customer satisfaction, brand image on consumer loyalty. To test the F occur together same effect between the variable x to the variable y.The results of customer satisfaction as an intervening variable to variable customer loyalty through brand image variable (-0.041), price (-0.026), and the quality of the product (-0.023). Description results show that the intervening variables affect consumer satisfaction can be expressed as a liaison between the variable variable brand image, price, and quality of products with variable customer loyalty. Keywords: Brand Image, Price, Product Quality, Customer Satisfaction, and Consumer Loyalty.